2016
DOI: 10.1590/0102-3772e32ne215
|View full text |Cite
|
Sign up to set email alerts
|

Não foi bom pai, nem bom marido: Conjugalidade e parentalidade em famílias separadas de baixa renda

Abstract: -This study aims to differentiate parental and marital roles of low-income separated parents with small children. This survey was conducted in a university school clinic of Psychology, based on qualitative methodology. Four mothers and three fathers participated in semi-structured individual interviews. Through thematic analysis, the outcomes showed the dynamic, paradoxical, and recursive reality of these families, with particularities and similarities to other socioeconomic contexts. Movements to maintain and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
0
6
0
3
Order By: Relevance
“…On the other hand, the teams' perception regarding the reactions of reluctance also indicates the couples' difficulty in looking at their own relationships. This difficulty is also recorded in the studies that, for decades, have observed the triangulation of children in their parents' conjugal problems (Féres-Carneiro, 1980;Juras & Costa, 2017). As a result, the participation in the program makes it possible for many couples to come to perceive aspects of their relationship, and patterns of conjugal functioning, of which they had previously been unaware.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the teams' perception regarding the reactions of reluctance also indicates the couples' difficulty in looking at their own relationships. This difficulty is also recorded in the studies that, for decades, have observed the triangulation of children in their parents' conjugal problems (Féres-Carneiro, 1980;Juras & Costa, 2017). As a result, the participation in the program makes it possible for many couples to come to perceive aspects of their relationship, and patterns of conjugal functioning, of which they had previously been unaware.…”
Section: Discussionmentioning
confidence: 99%
“…Equally, Bolsoni-Silva, Nogueira and Santos (2014) have described -based on a single case -the application and results of a structured group intervention that worked on the functional relationships between the couple, communication, the expression of affection and resolution of problems. Juras and Costa (2017) present the initial phase of a study that proposes a group psychosocial intervention with separated mothers and fathers with small children, but does not provide details of the intervention proposed. In a clinical perspective, a report was found of two interventions lasting a single session developed according to the cognitive-behavioral perspective, one of which was geared towards raising the couple's awareness of patterns of communication, and the other of which focused on presenting a model for resolving problems (Silva & Vandenberghe, 2009).…”
mentioning
confidence: 99%
“…A resolução dos conflitos conjugais pode beneficiar o exercício parental após a separação. Tendo em vista que a história da relação conjugal exerce influência na história da relação parental, quanto menor for o nível de conflito entre os pais, melhor será o exercício da parentalidade depois da separação, o que protege o desenvolvimento dos filhos (Juras & Costa, 2017;Oliveira & Crepaldi, 2018;Ponciano & Féres-Carneiro, 2017).…”
Section: Mulheres E a Separação Conjugal Na Contemporaneidadeunclassified
“…Entende-se que, uma vez que a mulher detenha a guarda exclusiva, pode vir a envolver-se com mais propriedade nos cuidados e educação das crianças. Nesse sentido, além das concepções de gênero quanto aos cuidados básicos, o distanciamento financeiro e o provimento também conduzem à minimização da responsabilidade e vínculos afetivos/interacionais de pais em relação aos filhos (Juras & Costa, 2016).…”
Section: Composição Familiarunclassified